2016
DOI: 10.1038/srep37198
|View full text |Cite
|
Sign up to set email alerts
|

Selective sweep on human amylase genes postdates the split with Neanderthals

Abstract: Humans have more copies of amylase genes than other primates. It is still poorly understood, however, when the copy number expansion occurred and whether its spread was enhanced by selection. Here we assess amylase copy numbers in a global sample of 480 high coverage genomes and find that regions flanking the amylase locus show notable depression of genetic diversity both in African and non-African populations. Analysis of genetic variation in these regions supports the model of an early selective sweep in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 36 publications
14
75
0
Order By: Relevance
“…If an (AMY1) 3 allele was the common ancestral structure for all modern humans, the initial amplification to higher gene copy number may have been selectively advantageous before the neolithic, consistent with a recent analysis of sequence data [Inchley et al, 2016]. Nevertheless, whether adaptive or neutral, a preneolithic expansion to higher copy number does not itself preclude subsequent adaptive value for copy number change after the neolithic [Perry et al, 2007].…”
Section: Discussionsupporting
confidence: 76%
“…If an (AMY1) 3 allele was the common ancestral structure for all modern humans, the initial amplification to higher gene copy number may have been selectively advantageous before the neolithic, consistent with a recent analysis of sequence data [Inchley et al, 2016]. Nevertheless, whether adaptive or neutral, a preneolithic expansion to higher copy number does not itself preclude subsequent adaptive value for copy number change after the neolithic [Perry et al, 2007].…”
Section: Discussionsupporting
confidence: 76%
“…After being exposed to saliva for 60 minutes (Figure 3H) the boiled starch granules were degrading. The results of this simple experiment are consistent with many studies which have shown that amylases are much more active on starch granules that are partially gelatinised than they are on intact starch granules 72,[74][75][76] . and linolenic), potentially from pine nuts.…”
Section: Foodsupporting
confidence: 90%
“…All higher primates have AMY1 ; however, the number of AMY1 genes duplicated at some point in the hominin lineage, which increased the efficiency of starch digestion due to greater capacity for amylase action. The timing of the duplications of the AMY1 gene in humans is unclear; it may have occurred after the modern human line branched off from the Neanderthals and Denisovans, although higher AMY1 copy numbers have also been detected in a pre‐Neanderthal ancestor . On exposure to saliva, even starch granules that have been only partially disrupted by cooking would be very susceptible to breakdown and very unlikely to survive to become embedded in dental calculus (Figure ).…”
Section: Categories Of Materials Recovered From Dental Calculusmentioning
confidence: 99%
“…Time to the Most Recent Common Ancestor (TMRCA) were also calculated for 10kbp sequences (Inchley et al 2016) surrounding each insertion site ( Supplemental Table S10, details in METHODS). Of the 24 insertions that are fixed or almost fixed in al modern populations, we selected those showing a TMRCA compatible with the split between AMH and HN/HD (TMRCA < 800 Kya) as potential candidates for selection/spread along the AMH lineage.…”
Section: Amh-specific Ris In Present-day Populationsmentioning
confidence: 99%
“…The time to the Most Recent Common Ancestor (TMRCA) of each 10kbp regions encompassing a given insertion was estimated as described elsewhere (Inchley et al 2016) based on 1000 Genomes sequences of AFR samples to avoid potential backwards biases due to the documented Neanderthal introgression in 28 Eurasians . All AFR individuals, and not only carriers of an insertion, were used for this calculations.…”
Section: Tmrca Estimates Of Genetic Regions Surrounding Amh-specific Rimentioning
confidence: 99%